2001
DOI: 10.1046/j.1365-2494.2001.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of harvest date and inoculation on the yield, fermentation characteristics and feeding value of forage pea and field bean silages

Abstract: Fraser, M. D., Fychan, A. R., Jones, R. (2001). The effect of harvest date and inoculation on the yield, fermentation characteristics and feeding value of forage pea and field bean silages. Grass and Forage Science, 56, (3), 218-230. Sponsorship: MAFF/Milk Development CouncilTwo experiments describe the ensiling potential of whole-crop forage peas (Pisum sativum) and field beans (Vicia faba). In Experiment 1, forage peas (cv. Magnus) and field beans (cv. Mayo) were harvested at 10, 12 and 14 weeks after sowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
33
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 32 publications
7
33
0
1
Order By: Relevance
“…Pea silage had the highest (P < 0.05) starch content, followed by FS and SS, respectively. In agreement with our findings, Fraser et al (2001) reported higher starch content for PS than for FS at a similar stage of maturity.…”
Section: Chemical Composition Of 45 D Silagessupporting
confidence: 93%
See 4 more Smart Citations
“…Pea silage had the highest (P < 0.05) starch content, followed by FS and SS, respectively. In agreement with our findings, Fraser et al (2001) reported higher starch content for PS than for FS at a similar stage of maturity.…”
Section: Chemical Composition Of 45 D Silagessupporting
confidence: 93%
“…In accordance with our results, Fraser et al (2001) reported higher CP levels of FS than PS at a similar stage of maturity. As expected, SCP was the main crude protein fraction in the three silages and most of that CP fraction was in the form of NPN.…”
Section: Chemical Composition Of 45 D Silagessupporting
confidence: 92%
See 3 more Smart Citations